ANALISIS IMPLEMENTASI MANAJEMEN PERSEDIAAN BAHAN BAKU PADA INDUSTRI KULINER DALAM PERSPEKTIF ETIKA BISNIS ISLAM - Sugeng Nugroho Hadi; Salihah Khairawati (Universitas Islam Bandung, 2020)
ABSTRACT Inventory is a resource that makes a company can carry out its production operations. Therefore it becomes imperative for companies to have the most appropriate inventory management model for things that need to be backed up. The culinary industry is an industry that requires the provision of processed raw materials, where each ingredient has different characteristics and shelf life. In the culinary industry, such as Waroeng Special Sambel